2010
DOI: 10.1080/00015458.2010.11680580
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to FDG-PET/CT Diagnostics and Post-Operative Monitoring of Patients with Mycotic Aneurysm of the Thoracic Aorta

Abstract: Bacterial infection of the aorta is a life threatening condition calling for timely diagnostics and therapy. In the short communication presented here, the authors offer a case report on a patient of 70 years of age with aneurysm of the descending aorta caused by salmonella. The advantages of a new diagnostic hybrid modality are demonstrated and also the possibility of using it in the course of long-term monitoring of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…Furthermore, FDG-PET/CT made an important contribution for monitoring response to antibiotic therapy. Similar results have been described by Spacek et al in their report [9]. FDG-PET has also been proposed as a tool to evaluate human TB uveitis [10].…”
Section: The Literature Evidence Of Fdg-pet In Monitoring Response Tosupporting
confidence: 65%
“…Furthermore, FDG-PET/CT made an important contribution for monitoring response to antibiotic therapy. Similar results have been described by Spacek et al in their report [9]. FDG-PET has also been proposed as a tool to evaluate human TB uveitis [10].…”
Section: The Literature Evidence Of Fdg-pet In Monitoring Response Tosupporting
confidence: 65%
“…Use of rifampin deserves special mention, because of its role in treating biofilm associated infection, such as S. aureus prosthetic vascular graft infections and preferential concentration in leucocytes leading to better drug delivery to the site of infection. Use of endovascular approach and implantation of stent grafts along with antibiotics has been shown to be beneficial for patients not suitable for conventional open surgery 17. This approach could also be used in a situation of impending rupture as a ‘bridge to surgery’.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, PET/CT imaging is a very sensitive imaging modality in the diagnosis of infection. In a few case reports, FDG-PET and PET/CT was found to be a useful diagnostic modality for the evaluation of suspected infected grafts (5,6,7,8). In a case report by Marion MD et al (9), the authors reported the mycobacterium abscessus infection of an infrainguinal vascular bypass prosthetic graft localized by FDG-PET/CT scan.…”
Section: Literature Review and Discussionmentioning
confidence: 99%